Conceptual Amelioration as a Response to Assumptions of Neutral Descriptive Language - LeBlanc, Christine (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2025)
Libraries are reliant on knowledge organization systems such as the Library of Congress Subject Headings to make information accessible to users. This article draws on writing in critical librarianship to highlight areas, particularly involving the description of people, where the language of classification can perpetuate harm, dehumanization, and misunderstanding. It also charts progress and criticism of the way we classify gender and sexuality, disability, race, and immigration status. The paper uses the work of analytic philosophers Sally Haslanger and Ludwig Wittgenstein to highlight the problems of treating classification terms as neutral descriptive language rather than inherently political and social concepts. Haslanger’s project of ‘conceptual amelioration’ is used to frame the ways libraries can and should acknowledge that the way language is organized has real-world impacts on the way members of a community coordinate, or interact, with each other. Identifying the ways we privilege assumptions from the dominant white, settler, heteronormative mainstream culture and recognizing them as a trained set of symbols can help us make localized decisions about language that are better for our communities of learning, our colleagues, and our library users.